2018
DOI: 10.1007/s00213-018-4843-6
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic targets for the treatment of alcohol use disorder

Abstract: The role of norepinephrine (NE) in the development of alcohol use disorder (AUD) has been studied over the past several decades. However, the NE system has been largely ignored for many years as a potential target for medication development for AUD. More recently, preclinical and clinical studies have demonstrated the potential value of targeting NE signaling for developing new pharmacological treatments for AUD. This review contributes to a special issue of Psychopharmacology focused on promising targets for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 100 publications
0
56
0
6
Order By: Relevance
“…Although the model has not yet been translated to validated clinical applications, it informed the development of the Addictions Neuroclinical Assessment, a framework that uses neuropsychological data that correspond to the three stages of the neurobiological opponent process model to classify the individual differences in AUD to improve diagnosis and treatment 43. The model does imply specific treatment targets, such as corticotropin releasing factor44,45 and alpha 1 -noradrenergic systems 46. Simpson and colleagues found clinical benefit from prazosin, an alpha 1 antagonist, in participants with an alcohol dependence diagnosis 47.…”
Section: Neurobiological Theoriesmentioning
confidence: 99%
“…Although the model has not yet been translated to validated clinical applications, it informed the development of the Addictions Neuroclinical Assessment, a framework that uses neuropsychological data that correspond to the three stages of the neurobiological opponent process model to classify the individual differences in AUD to improve diagnosis and treatment 43. The model does imply specific treatment targets, such as corticotropin releasing factor44,45 and alpha 1 -noradrenergic systems 46. Simpson and colleagues found clinical benefit from prazosin, an alpha 1 antagonist, in participants with an alcohol dependence diagnosis 47.…”
Section: Neurobiological Theoriesmentioning
confidence: 99%
“…Thus, we predicted that the adolescent CORT-treated rats would have a reduced sensitivity to α 2A R-mediated signaling, which could result in an increase in norepinephrine release and post-synaptic signaling in the brain, as the normal autoreceptor-mediated brake on noradrenergic-transmission would be impaired. Given the large literature on the involvement of heightened noradrenergic signaling, particularly in the amygdala, for both stress- and alcohol-related behaviors, including the potential clinical use of α 2A AR agonists as a treatment for alcohol use disorders [33,34,35], GRK2-mediated phosphorylation of α 2A AR after adolescent CORT exposure is a strong candidate as a mediator of increased motivation for alcohol. Therefore, we decided to directly test if inhibition of GRK2 in the amygdala could reduce alcohol-motivated behaviors in adolescent CORT- or H 2 O-exposed rats.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, increased phosphorylation of four serine residues in the third intracellular loop of the α2AR, which are a GRK2 substrate, was of particular interest, due to evidence pointing to the potent role of adrenergic signaling, particularly in the amygdala, in ethanol drinking and seeking. It has long been recognized that the noradrenergic system plays a critical role in the development of alcohol use disorders, but only recently has interest been revitalized in targeting this system with respect to AUD treatment [34]. Preclinical studies have shown that downregulation of noradrenergic signaling, via α 2A R agonism (clonidine; [35]), or antagonism of α1AR (prazosin; [41]) or βAR (propranolol; [42]), reduces ethanol drinking and seeking in high-consuming animals.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the alpha-1 antagonists prazosin and doxazosin are effective in a preclinical model of stress-induced alcohol seeking (Lê et al, 2011; Funk et al, 2016), and there are also promising clinical data in humans with alcohol use disorders (Fox et al, 2012; Haass-Koffler et al, 2018). The brain circuitry underlying these effects of alpha-1 antagonists is unclear, however.…”
Section: Discussionmentioning
confidence: 99%
“…Prazosin also reduces yohimbine-induced brain activation in areas implicated in stress-induced reinstatement (Bing et al, 1992; Stone and Zhang, 1995; Funk et al, 2016). Consistent with this, alpha-1 adrenoceptor antagonists including prazosin have received attention as treatments for alcohol use disorders and chronic stress conditions such as post-traumatic stress disorder, which frequently co-occur with alcoholism (Walker et al, 2008; Rasmussen et al, 2009; Green, 2014; Simpson et al, 2015; Haass-Koffler et al, 2018).…”
Section: Introductionmentioning
confidence: 92%